The antiquity of pain: agency, identity, and revenge in the elaboration of fiction as a reparation mechanism - Perea, Fabián (2023)
By means of a narratological exercise established through the reading of Beloved and Medea, this article seeks to understand the mechanisms that form tragedy as a literary genre, to analyze how fiction could constitute a resource for symbolic reparation of the agency of systematically marginalized communities, by virtue of the use of revenge as a device of vindication.